Relationship between albumin and osteoporosis in patients with type 2 diabetes mellitus - Zhao, Hang; Qi, Cuijuan; Zhang, Yunjia; Yang, Liqun; Ren, Luping; Chen, Shuchun (Frontiers in Endocrinology, 2025)
PurposeThis study aimed to investigate whether low albumin levels are a risk factor for osteoporosis (OP) in patients with type 2 diabetes mellitus (T2DM).Patients and methodsThis study included adult patients with T2DM hospitalized at the Hebei General Hospital in China between 2019 and 2020. Patients were divided into groups based on OP to explore the differences between the two groups and stratified by sex. Confounding factors were screened based on the statistical results and clinical practice, and regression analysis was used to explore the relationship between albumin levels and OP.ResultsIn total, 125 patients (68 men and 57 women) with T2DM were included in this study. Triglyceride and high-density lipoprotein cholesterol levels significantly differed between groups. In the low-albumin group, after adjusting for all confounding factors, the P value was 0.041 and the odds ratio (OR) was 4.608 [95% confidence interval (CI): 1.063, 19.063] compared with that in the normal-albumin group. Among male patients, considering all confounding factors, the OR was 12.936 (95% CI: 1.130, 148.125) and P = 0.040 in the low-albumin group compared with that for the normal-albumin group. No such relationship was found in female patients.ConclusionA low albumin level is a risk factor for OP in the total population and in male patients but not in female patients. Therefore, albumin levels should be considered when controlling glucose levels in patients with T2DM.